Taxes in Cities - Marius Brülhart; Sam Bucovetsky; Kurt Schmidheiny (Center for Economic Studies and ifo Institute (CESifo), 2014)
Most cities enjoy some autonomy over how they tax their residents, and that autonomy is typically exercised by multiple municipal governments within a given city. In this chapter, we document patterns of city-level taxation across countries, and we review the literature on a number of salient features affecting local tax setting in an urban context. Urban local governments on average raise some ten percent of total tax revenue in OECD countries and around half that share in non-OECD countries. We show that most cities are highly fragmented: urban areas with more than 500,000 inhabitants are divided into 74 local jurisdictions on average. The vast majority of these cities are characterized by a central municipality that strongly dominates the remaining jurisdictions in terms of population. These empirical regularities imply that an analysis of urban taxation needs to take account of three particular features: interdependence among tax-setting authorities (horizontally and vertically), jurisdictional size asymmetries, and the potential for agglomeration economies. We survey the relevant theoretical and empirical literatures, focusing in particular on models of asymmetric tax competition, of taxation and income sorting and of taxation in the presence of agglomeration rents.
Keywords: H71; H73; R28; R51; 330; cities; taxes; tax competition; fiscal federalism; agglomeration; sorting